Progression of SEI & SEM Final Year Projects. - Mohd. Amri Md. Yunus, editor 486325; Herlina Abdul Rahim, 1973-, editor 502013; Shafishuhaza Sahlan, editor 502014; Khairul Hamimah Abas, editor 399952; Ahmad Athif Mohd. Faudzi, contributor 617569; Amirah 'Aisha Badrul Hisham, 1988-, contributor 581798; Chan, Kok Teik, 1989-, contributor 617287; Cheng, Siong Lim, contributor 647610; Chin, Ching Long, contributor 647611; Kai, Wee Cheu, contributor 647612; Marwan Nafie Minjal, contributor 647613; Mohamad Hafis Izran Ishak, contributor 439403; et al. (Johor Bahru, Johor : PUSAT PENGURUSAN PENYELIDIKAN (RMC) & PENERBIT UTM PRESS, 2014)
Includes bibliographical references and index.